Analysis Sentimen Dampak Cyberbullying pada Penggemar K-Pop Melalui Aplikasi Twitter Menggunakan Metode Naïve Bayes - Noris, Shandi (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Cyberbullying is a violent act committed by someone against another person in an electronic media or the internet. The impact of cyberbullying is that it affects the victim's mentality, not a few victims of bullying end up committing suicide because they cannot stand the pressure of bullying. Korean Pop or better known as K-Pop is starting to dominate the Music Industry in Indonesia today. K-Pop can also be recognized by the emergence of K-Pop fan clubs on social media that provide all information about K-Pop artists to their fans. Indonesia is ranked 3rd with the most tweets about K-Pop. Sentiment analysis in Indonesian is a technique or method used to identify how a sentiment is expressed into a text and how a sentiment can be categorized as a positive or negative sentiment. The method used in this study is the Naïve Bayes Method. In the Naïve Bayes calculation process, the results of this study can be classified as positive, negative and neutral from the opinions of Twitter users.